Admissibility of Fractional Order Descriptor Systems Based on Complex Variables: An LMI Approach - Xuefeng Zhang; Yuqing Yan (Fractal and Fractional, 2020)
This paper is devoted to the admissibility issue of singular fractional order systems with order <semantics> α ∈ ( 0 , 1 ) </semantics> based on complex variables. Firstly, with regard to admissibility, necessary and sufficient conditions are obtained by strict LMI in complex plane. Then, an observer-based controller is designed to ensure system admissible. Finally, numerical examples are given to reveal the validity of the theoretical conclusions.